THE IMPACT OF INTERVENTION ON INVENTORY-CONTROL MECHANISM - Nevi Danila (Akutansi Bisnis & Manajemen ( ABM ), 2001)
We find that government intervention by sales of US dollar in the 1985-1987 period is insignificant. This means the dealers did not believe the signal, which was given by the government through coordinated government intervention. Intervention by purchase of the US dollar was significant with a positive but incorrect sign. The positive sign means that the dealers shifted down the quote to discourage their customers from selling US dollars (buy DM and Yen) and to encourage them to buy US dollars (sell DM and Yen) as they anticipated the US dollar would depreciate. The purchase of US dollar signal led to the market believing that the government had an intention to appreciate the dollars in the future. Thus, the dealers reacted in the opposite direction to the government?s intention. We believe this was supposed due to the lack of credibility of the government intervention. We also note that the large scale of G-3 (Japan, Germany and USA) intervention to support the US dollar (purchasing dollars against DM) after the stock market crash of October 1987 was perceived by market participants as a commitment of US to prevent a post-crash liquidity crisis rather than a commitment to support the dollars (Dominguez, 1990, p. 139). In summary, the intervention during this period (1985 to 1987) was not credible. Consequently, the intervention was not effective. The ineffectiveness of the intervention was due to the lack of commitment of the monetary authorities (DeGrauwe, 1996). The G-5 needed to hasten their efforts to build a more credible and effective international monetary regime or they should have committed themselves fully to policy coordination (Funabashi, 1988, p.246)